A STUDY OF THE INFLUENCE OF 650 nm LASER INTERFERENCE ON VISIBLE LASER LIGHT COMMUNICATION SYSTEM - Laksono, Pranoto Budi (Department of Computer Engineering, Universitas Wiralodra, 2021)
Visible Laser Light Communication System (VLLC) is a wireless communication system, using laser as the medium. In the data transfer process, it is possible to have optical interference where 2 laser beams coincide with one point on the reflector. Research on the effect of laser source interference has been carried out by several researchers including mitigation actions to reduce its effects. This experiment uses 2 optical distance sensors that produce a laser with a wavelength of 650 nm with a power <=4.1 mW and with the direction of the laser beam both of them cross each other. To determine the effect of the interference of two laser beams when crossing the communication process in the visible light communication system, a reflector is used which can capture the two laser beams and the reflector can be shifted gradually so that a condition can be obtained where the two laser beams meet at one point. From the measurements made at the points after the laser beam crossing, the measurements at the point where the beam crossed, and the measurements at the points before the beam crossing, it was obtained data, at the exact point where the laser beam crossed the interference occurred, which is indicated by unstable output voltage of the two lasers, so that communication at the point of intersection is disrupted. However, if outside the point of contact both before and after the point of contact, interference and communication systems will not occur.